BIMBINGAN KELOMPOK TEKNIK DISKUSI KELOMPOK UNTUK MENINGKATKAN KEMAMPUAN PERENCANAAN KARIR BAGI MAHASISWA CALON PENDETA - Milkatahasi, Milkatahasi; Soesilo, Tiritjahjo Danny; Windrawanto, Yustinus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted at GKSI Dompon. This research aims to prove that group discussion technique guidance can significantly improve the career planning abilities of student pastors at GKSI Dompon. The type of research used is Quasi Experimental Design with the Equivalent Control Group Design design method. The subjects of this research were 8 prospective priest students, all of whom had moderate career planning abilities. These 8 students were divided into 2 groups, namely 4 students in the experimental group and 4 students in the control group. This research uses group guidance, group discussion techniques and data collection methods using a career planning scale based on Doland Super theory. The data analysis technique uses the Mann Whitney Test. Asimp Results. The results of the Sig analysis (2-tailed) were 0.021<0.05, with an average post-test ranking for the control group of 2.50 and an average post-test ranking for the experimental group of 6.50. Thus, it can be concluded that there has been a significant increase in the field of career planning among prospective priest students, after being provided with group guidance services on group discussion techniques. The conclusion of this research is that technical guidance group discussion groups can improve the career planning abilities of prospective priest students.